DEGRO/DGK guideline for radiotherapy in patients with cardiac implantable electronic devices = Leitlinie der DEGRO/DGK zur Strahlentherapie bei Patienten mit kardialen implantierten elektronischen Geräten - Gauter-Fleckenstein, Benjamin; Schimpf, Rainer; Steil, Volker; Wenz, Frederik (Strahlentherapie und Onkologie, 2015)
An increasing number of patients undergoing radiotherapy (RT) have cardiac implantable electronic devices [CIEDs, cardiac pacemakers (PMs) and implanted cardioverters/defibrillators (ICDs)]. Ionizing radiation can cause latent and permanent damage to CIEDs, which may result in loss of function in patients with asystole or ventricular fibrillation. Reviewing the current literature, the interdisciplinary German guideline (DEGRO/DGK) was developed reflecting patient risk according to type of CIED, cardiac condition, and estimated radiation dose to the CIED. Planning for RT should consider the CIED specifications as well as patient-related characteristics (pacing-dependent, previous ventricular tachycardia/fibrillation). Antitachyarrhythmia therapy should be suspended in patients with ICDs, who should be under electrocardiographic monitoring with an external defibrillator on stand-by. The beam energy should be limited to 6 (to 10) MV CIEDs should never be located in the beam, and the cumulative scatter radiation dose should be limited to 2 Gy. Personnel must be able to respond adequately in the case of a cardiac emergency and initiate basic life support, while an emergency team capable of advanced life support should be available within 5 min. CIEDs need to be interrogated 1, 3, and 6 months after the last RT due to the risk of latent damage.
Gesehen am 01.12.2017